2019
DOI: 10.1007/s11669-019-00717-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modeling of the La-Co-O System

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…According to the reported La/Co/O phase diagram (Figure ), La 2 CoO 4 (LCO) melts incongruently at around 2050 K with a eutectic temperature of 1885 K . Therefore, LCO single crystals can only be grown within this narrow temperature range, using a melt with a Co:La molar ratio approximately between 1.22:1 and 4:1, corresponding to the B–C line in the phase diagram in Figure .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…According to the reported La/Co/O phase diagram (Figure ), La 2 CoO 4 (LCO) melts incongruently at around 2050 K with a eutectic temperature of 1885 K . Therefore, LCO single crystals can only be grown within this narrow temperature range, using a melt with a Co:La molar ratio approximately between 1.22:1 and 4:1, corresponding to the B–C line in the phase diagram in Figure .…”
Section: Resultssupporting
confidence: 74%
“…According to the reported La/Co/O phase diagram (Figure 2), La2CoO4 melts incongruently at around 2050 K with an eutectic temperature of 1885K. 30 Therefore, LCO single crystals can only be grown within this narrow temperature range, using a melt with a Co:La molar ratio approximately between 1.22:1 and 4:1, corresponding to the B-C line in the phase diagram in Figure 2). Generally, the few works reported in the literature on the growth of La2CoO4 single crystals have been carried out by the Travelling Solvent zone method, using an increased Co concentration for the travelling solvent.…”
Section: Crystal Growthmentioning
confidence: 99%
“…[46][47][48] For the latter, previously reported calorimetric data 46,47,49 agree fairly well with each other as well as with the recent thermodynamic assessment results. 50 On the contrary, the heat capacity calculated for LaCoO 3 by Thakur et al 48 significantly exceeds the results of others 46,47 (see Fig. 7), especially taking into account that Thakur et al 48 reported C , V so C P values recalculated from their data should be even higher due to the thermal expansion of the crystal lattice.…”
mentioning
confidence: 61%
“…The additional spinel nanoparticles are formed because the precursors in the CVS setup presented here are evaporated with a small excess of the transition metal acetylacetonate instead of perfect equimolar evaporation. The resulting formation of an additional spinel phase corresponds to the equilibrium phase diagram of the LaFeO 3 and LaCoO 3 system.…”
Section: Resultsmentioning
confidence: 97%